Mucormycosis and acute kidney injury - Krishan L Gupta; Aakriti Gupta (Society of Diabetic Nephropathy Prevention, 2012)
Mucormycosis, although said to be less common than candidiasis and aspergillosis is becoming increasingly associated with many co-morbid conditions and immunosuppression. Renal involvement, rarely reported previously, has also been documented with increasing frequency in recent times in both diseased as well as apparently healthy individuals. The kidneys may be involved in disseminated disease or have an isolated involvement for unexplained reasons. The manifestations are very serious particularly in patients with bilateral renal mucormycosis who often develop acute kidney injury and usually have a fatal outcome. The diagnosis of the renal mucormycosis is based on renal histology sections of renal biopsy or nephrectomised kidneys. Imaging with computerised tomography with contrast is of tremendous help in early identification of these cases before histological diagnosis. Once diagnosis is established, prompt treatment with antifungal medication, including Amphotericin-B (and its lipid formulations) and posaconazole, and removal of infected tissue is necessary to save from otherwise fatal infection.